Biomonitoring of benthic organisms for coastal protection: a checklist study from Pantai Remis and Blue Lagoon on the west coast of Peninsular Malaysia - Ahmad Wakid, Sarini; Syazwan, Wan Mohd; Abd Aziz, Nor Azwady; Mustafa, Muskhazli; Okamura, Hideo; Horie, Yoshifumi; Ong, Meng Chuan; Ismail, Mohamad Saupi; Setyawan, Ahmad Dwi; Chew, Jia Ming; Yap, Chee Kong (Universal WISER Publisher, 2023)
The objective of the study was to provide an updated checklist of benthic marine organisms in Pantai Remis (Selangor) and Blue Lagoon (Negeri Sembilan) in November 2022. The research areas comprised a total of 26 species of marine benthic organisms, which were divided into 12 orders, 18 families, and 22 genera. Benthic macrophytes formed the largest group (11 species), followed by other benthic macrofauna (molluscs, with eight species). In addition, three coral species, two gastropods, and two crabs were also recorded. The findings revealed that both sites are fertile and suitable habitats for marine benthic organisms. The established checklist of benthic organisms can serve as an ongoing basis for future reference as part of our efforts to develop coastal marine ecosystem management and conservation on the west coast of Peninsular Malaysia. In summary, the checklist of benthic organisms provides the basic information that is much needed for the protection of coastal ecosystems.